Peran, Strategi, dan Tantangan Lembaga Swadaya Masyarakat (LSM) Lingkungan dalam Menyelesaikan Permasalahan Pengelolaan Sampah - Muthiara Angraeni; Wardatul Azizah; Alif Marta Nurhadi (Advances In Education Journal, 2025)
Waste management in Indonesia is a critical issue affecting public health and environmental sustainability, with annual waste production reaching millions of tons, while infrastructure and public awareness remain inadequate. This writing is urgent to highlight the role of environmental non-governmental organizations as government partners in addressing this issue, given that regulations like the waste management law have not been fully effective. The research employs a normative juridical approach through library studies on legislation and related institutional reports. The results indicate that environmental non-governmental organizations play roles in advocacy, education, and community empowerment, with strategies such as coordination with government and fundraising, despite challenges like permitting difficulties and low community participation. In conclusion, stronger collaboration is needed to achieve sustainable waste management.